Brits behaving badly: template analysis of newspaper content - Andriotis, Konstantinos (My University, 2010)
This study explores the ways in which public debates about the sexual, drinking and risk taking behaviour of young British travellers, who participate in trips organised to Greek summer resorts exclusively by Club 18-30, have been interpreted, and framed, within print media (British newspapers). Using a template analysis approach four themes emerged, namely binge drinking, sexual behaviour, risk taking and host reactions. These themes are discussed in relation to the methodology adopted, and the findings of previous research, and policies for risk-taking decrease, and solutions to reduce the problems posed by young tourists' antisocial behaviour in summer Greek resorts, are provided.
Keywords: Youth travel; Antisocial behaviour; Binge drinking; Casual sex; Risk taking; Template analysis